A SIMPLE MATHEMATICAL MODEL OF NON-SMALL CELL LUNG CANCER INVOLVING MACROPHAGES AND CD8+ T CELLS - Lourenço, Edgard [UNESP]; Rodrigues, Diego S.; Antunes, Maria E. [UNESP]; Mancera, Paulo F.A. [UNESP]; Rodrigues, Guilherme [UNESP] (World Scientific Publishing, 2023)
We analyze biological processes interconnected to the tumor microenvironment development of non-small cell lung cancer (NSCLC), considering a proposed ordinary differential equation (ODE) model. The concepts of cancer as a disease, the cellular heterogeneity of the tumor microenvironment composition, and the macrophage cell epigenetic heterogeneity are presented, and the dynamics of the relations between them, the cytotoxic T cells and the neoplasm cells are explored. The apoptosis rate of the macrophage cells which present protumor characteristics is revealed as having a key role in the local stability of the ODE model. Furthermore, the hypothesis on the relevance of the CD8+ T cells in assisting the macrophage cells to control the tumor volume indicates a immunotherapeutic treatment possibility that considers both of these cells effectively.
Keywords: Cancer Dynamics; Macrophages; Sensitivity Analysis; TIL Therapy